Synthesis of high-soluble and non-fluorescent perylene derivatives and their effect on the contrast ratio of LCD color filters. (January 2017) - Kim, Jeong Yun; Hwang, Tae Gyu; Kim, Se Hun; Namgoong, Jin Woong; Kim, Ji Eon; Sakong, Chun; Choi, Jun; Lee, Woosung; Kim, Jae Pil
Abstract: We designed and synthesized perylene-based dyes for dye-based LCD color filters that highly soluble in organic industrial solvents, exhibit very weak fluorescence, and can be easily synthesized due to their simple molecular structures. The synthesized dyes were designed containing methoxy groups in the terminal-, bay-, or both positions for developing fluorescence quenched dyes. And, dyes with strong fluorescence and similar molecular structures to the fluorescence quenched dyes were also synthesized to clearly compare and analyze the effect of fluorescence on the optical properties. Finally, we fabricated dye-based color filters using the synthesized dyes and analyzed the optical performances of the color filters. The methoxy group in the bay-substituents has an enormous effect on the fluorescence quenching without the conspicuous influences on molecular behavior or dye aggregation. And, the fluorescence quenched dyes have remarkable effects in minimizing the increment of minimum brightness and prohibiting the contrast ratio decrease. Graphical abstract: Highlights: High-soluble and non-fluorescent perylene dyes are designed and synthesized. The designed dyes are containing methoxy groups for fluorescence quenching. Dye-based color filters are fabricated with the synthesized dyes. Non-fluorescent dyes have effects in minimizing the decrease of contrast ratio.